The Meaning of the Principal's Transformational Leadership Style for Teacher Motivation in Adapting to the Philosophy and Approach of the Independent Curriculum - Nofry Frans; Vera Wahani (Civiliza Publishing, Indonesia., 2025)
This study aims to understand the significance of the principal's transformational leadership style for teacher motivation in adapting to the philosophy and approach of the Independent Curriculum at SMA Unklab. This study uses a qualitative phenomenological approach to understand the significance of the principal's transformational leadership style on teacher motivation in adapting to the philosophy and approach of the Independent Curriculum at SMA Unklab. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model which includes data reduction, presentation, and extracting meaning. Data validity was guaranteed through triangulation of sources and methods to obtain an authentic understanding of the role of the principal's leadership as a driver of teacher motivation and adaptation in the implementation of the Independent Curriculum. The results show that the principal's leadership at SMA Unklab plays a significant role in increasing teacher motivation to adapt to the philosophy and approach of the Independent Curriculum. The principal acts as an inspirational figure who is open to new ideas and is able to build a collaborative work culture in the school environment. Through consistent role models and support, teachers feel valued and encouraged to innovate in the learning process. Leadership oriented towards the values ​​of togetherness and the spirit of change strengthens teachers' professionalism and commitment to realizing meaningful and independent learning.